Cellulolytic RoboLector – towards an automated high-throughput screening platform for recombinant cellulase expression. Issue 1 (December 2017) - Mühlmann, Martina; Kunze, Martin; Ribeiro, Joaquim; Geinitz, Bertram; Lehmann, Christian; Schwaneberg, Ulrich; Commandeur, Ulrich; Büchs, Jochen
Abstract Background Cellulases are key player in the hydrolyzation of cellulose. Unfortunately, this reaction is slow and a bottleneck in the process chain from biomass to intermediates and biofuels due to low activities of the enzymes. To overcome this draw back, a lot of effort is put into the area of protein engineering, to modify these enzymes by directed evolution or rational design. Huge clone libraries are constructed and have to be screened for improved variants. High-throughput screening is the method of choice to tackle this experimental effort, but up to now only a few process steps are adapted to automated platforms and little attention has been turned to the reproducibility of clone rankings. Results In this study, an extended robotic platform is presented to conduct automated high-throughput screenings of clone libraries including preculture synchronization and biomass specific induction. Automated upstream, downstream and analytical process steps are described and evaluated usingE. coli andK. lactis as model organisms. Conventional protocols for media preparation, cell lysis, Azo-CMC assay and PAHBAH assay are successfully adapted to automatable high-throughput protocols. Finally, a recombinantE. coli celA2 clone library was screened and a reliable clone ranking could be realized. Conclusion The RoboLector device is a suitable platform to perform all process steps of an automated high-throughput clone library screening for improved cellulases. On-line biomass growth measurement controlling liquid handling actions enables fair comparison of clone variants.